Substate dictatorship : networks, loyalty, and institutional change in the Soviet Union - Gorlizki, Yoram; Khlevni͡uk, O. V. (Oleg Vitalʹevich) (Yale-Hoover series on authoritarian regimes., 2020)
An essential exploration of how authoritarian regimes operate at the local level.